Shade provision and its influence on water intake and drinking behaviour of Nellore cattle in feedlot in a tropical environment - M. Jordana Rivero; Julio C. Pascale Palhares; Taisla Inara Novelli; Luciane Silva Martello; Simón Pérez-Márquez; Andrew S. Cooke (PLoS ONE, 2025)
Heat stress is a significant challenge in tropical beef production systems, affecting feed intake, water intake, and overall animal welfare. This study aimed to evaluate the impact of shade provision on the water intake and drinking behaviour of Nellore steers (Bos indicus) in a tropical feedlot environment. A total of 47 steers (~450 kg body weight) were allocated into two groups: one with access to shade (+S) and another without (-S). Individual water intake, drinking behaviour (e.g., frequency, daily patters), and animal performance were monitored over 83 days using automated recording systems. Results showed that -S steers consumed 8% more water per day (p < 0.001), made more frequent visits to the water trough (p < 0.001), but drank less per visit (p < 0.001) and overall spend 39% more time per day drinking (p < 0.001) compared to the + S steers. Despite these differences in drinking behaviour, average daily gain and feed intake did not differ between groups (p > 0.05). Environmental factors like temperature, humidity, and solar radiation affected water intake in both groups. Higher air temperatures increased water intake by boosting drinking frequency, while higher relative humidity reduced water intake by decreasing visit frequency. Shade provision reduced water demand per unit of body weight gain, improving water-use efficiency. These findings suggest that while shade may not directly enhance body weight gain, it can optimise drinking behaviour, reduce water intake, and improve animal welfare in tropical beef production systems.